Download presentation

Presentation is loading. Please wait.

Published byMargery Harris Modified over 6 years ago

1
Part 2

2
Review… Solve the following system by elimination: x + 2y = 1 5x – 4y = -23 (2)x + (2)2y = 2(1) 2x + 4y = 2 5x – 4y = -23 7x = -21 x = -3 x + 2y = 1 -3 + 2y = 1 2y = 4 y = 2 (-3, 2)

3
What do you think you should do to solve this system? 4x + 5y = 7 6x – 2y = -18 (2)4x + (2)5y = (2)7 8x + 10y = 14 (5)6x – (5)2y= (5)-18 30x – 10y = -90 Can you multiply one of the equations to eliminate a variable? We will need to multiply BOTH equations to eliminate one of the variables. Since the “y” has opposite signs, what can we multiply the 1 st equation by and what can we multiply the 2 nd equation by to eliminate the “y”s? We can multiply the 1 st equation by 2 so it will become “10y.” We can multiply the 2 nd equation by 5 so it will become “-10y.”

4
8x + 10y = 14 30x – 10y = -90 38x = - 76 x = -2 4x + 5y = 7 4(-2) + 5y = 7 -8 + 5y = 7 5y = 15 y = 3 Now we have the system set up so we can solve it. Solve the system by adding. Now substitute “-2” into one of the ORIGINAL equations and solve for “y.” The solution to the system is (-2, 3).

5
3x + 2y = 10 2x + 5y = 3 (2)3x + (2)2y = (2)10 (-3)2x + (-3)5y = (-3)3 6x + 4y = 20 -6x – 15y = -9 -11y = 11 y = -1 Solve the following system by elimination. What do we need to multiply each equation by in order to eliminate one of the variables? Let’s eliminate the “x” variable. Multiply the 1 st equation by 2 to get “6x.” Multiply the 2 nd equation by -3 to get “-6x.” Remember, the signs will need to have opposite values. 3x + 2y = 10 3x + 2(-1) = 10 3x – 2 = 10 3x = 12 x = 4 The solution to the system is (4, -1).

Similar presentations

© 2021 SlidePlayer.com Inc.

All rights reserved.

To make this website work, we log user data and share it with processors. To use this website, you must agree to our Privacy Policy, including cookie policy.

Ads by Google